Problems and prospects of quality education on tourism in Bangladesh: a particular emphasis on the tourism and hospitality management (THM) department of The People’s University of Bangladesh (PUB) - Sarker, Jashim Uddin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.